AB0494 Filgotinib (GLPG0634), a Selective JAK1 Inhibitor, Shows Similar PK and PD Profiles in Japanese and Caucasian Healthy Volunteers. (9th June 2015) - Namour, F.; Vayssière, B.; Galien, R.; Fagard, L.; Van der Aa, A.; Harrison, P.; Tasset, C.
Abstract : Background: Filgotinib is an oral, selective Janus kinase 1 (JAK1) inhibitor combining a favorable safety profile and clinical efficacy in patients after 4 weeks of dosing with rheumatoid arthritis (RA) with a rapid onset of action. Its once-daily oral administration is supported by the long half-life of an active metabolite with the same JAK1 selectivity profile as the parent compound. Given ethnicity may cause for differences in drug metabolism and pharmacokinetics (PK), and pharmacodynamics (PD) resulting in variability in clinical response, filgotinib was studied in Japanese healthy volunteers to evaluate the potential for different dosing requirements compared to Caucasians. Objectives: Compare the PK, PD and safety of filgotinib in Japanese to Caucasian healthy volunteers at 200 mg filgotinib. Methods: In a single-center Phase 1 study, 2 panels of 10 Japanese (1st and 2nd generation residing outside Japan for less than 5 years) and 10 Caucasian healthy volunteers received once daily 200 mg filgotinib or placebo for 10 days. The PK of filgotinib and its active metabolite were evaluated, and the overall PD of the two moieties was assessed in whole blood using ex vivo IL-6 induced phosphorylation of STAT1 (pSTAT1) as biomarker for JAK1 activity and GM-CSF induced phosphorylation of STAT5 (pSTAT5) for JAK2 activity. Standard safety assessments were performed throughout the study duration. Results: Steady state in filgotinib plasma concentrations was reached in 2 days in both Japanese and Caucasian volunteers with half-lives of 6 and 11 hours, respectively. In both ethnic groups, the active metabolite showed plasma concentrations well exceeding those of filgotinib with half-life values ranging of 17-20 hours and overall exposures for filgotinib and its metabolite being the same between the populations. In both ethnic groups, IL-6 induced pSTAT1 was inhibited over the entire 24 hour post-dosing period, with maximum inhibition observed between 1 and 5 hours post dose. No relevant inhibition of JAK2 activity was observed in Japanese and Caucasian healthy volunteers confirming the JAK1 over JAK2 selectivity of filgotinib. In Japanese healthy volunteers, filgotinib was generally safe and well tolerated with no relevant differences in safety profile as compared to Caucasian healthy volunteers. Conclusions: Filgotinib showed comparable PK, PD and safety profiles in Japanese and Caucasian healthy volunteers. The similarity in the PK and PD response suggests that there are no relevant differences among the groups in drug metabolism or sensitivity to selective inhibition of JAK1. Thus, these data support that filgotinib could be safely administered without dose adjustment to Japanese RA patients. Disclosure of Interest: F. Namour Shareholder of: GALAPAGOS, Employee of: GALAPAGOS, B. Vayssière Employee of: GALAPAGOS, R. Galien Shareholder of: GALAPAGOS, Employee of: GALAPAGOS, L. Fagard Employee of: GALAPAGOS, A. Van der Aa Shareholder of: GALAPAGOS, Employee of: GALAPAGOS, P. Harrison Shareholder of: GALAPAGOS, Employee of: GALAPAGOS, C. Tasset Shareholder of: GALAPAGOS, Employee of: GALAPAGOS